Micro a novel - Crichton, Michael, 1942-2008.; Preston, Richard, 1954-; Lloyd, John Bedford ([New York] : Harper Audio, 2011)
In Cambridge, Massachusetts, seven graduate students at the forefront of their fields are recruited by a pioneering microbiology start-up. Nanigen MicroTechnologies dispatches the group to a mysterious lab in Hawaii, where they are promised access to tools that will open a whole new scientific frontier. But once in the Oahu rain forest, the scientists are thrust into a hostile wilderness that reveals profound and surprising dangers at every turn.
Title from container.
Duration: 14:00:00.
Read by John Bedford Lloyd.
Compact disc.
Keywords: Microbiologists -- Fiction; Nanotechnology -- Fiction; Oahu (Hawaii) -- Fiction; Audiobooks; Suspense fiction